In situ TEM modification of individual silicon nanowires and their charge transport mechanisms. (2nd October 2020) - Alam, Sardar B; Andersen, Christopher R; Panciera, Federico; Nilausen, Aage A S; Hansen, Ole; Ross, Frances M; Mølhave, Kristian
Abstract: Correlating the structure and composition of nanowires grown by the vapour-liquid-solid (VLS) mechanism with their electrical properties is essential for designing nanowire devices. In situ transmission electron microscopy (TEM) that can image while simultaneously measuring the current–voltage ( I–V ) characteristics of individual isolated nanowires is a unique tool for linking changes in structure with electronic transport. Here we grow and electrically connect silicon nanowires inside a TEM to perform in situ electrical measurements on individual nanowires both at high temperature and upon surface oxidation, as well as under ambient conditions. As-grown, the oxide-free nanowires have nonlinear I–V characteristics. We analyse the I–V measurements in terms of both bulk and injection limited transport models, finding Joule heating effects, bulk-limiting effects for thin nanowires and an injection-limiting effect for thick wires when high voltages are applied. When the nanowire surface is modified by in situ oxidation, drastic changes occur in the electronic properties. We investigate the relation between the observed geometry, changes in the surface structure and changes in electronic transport, obtaining information for individual nanowires that is inaccessible to other measuring techniques.